Synthesis, IR characterization and antioxidant capacity of Cu(II) complexes with amino acids and melatonin - Ljubijankić, Sead; Galijašević, Semira; Davidović-Plavšić, Biljana; Balaban, Milica; Ljubijankić, Nevzeta (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2022)
In this paper, the reactions of anhydrous copper(II) chloride in methanolic solution with alanine, glycine, histidine, L-tryptophan, and melatonin were investigated and the resulting products were characterized by FTIR spectroscopy. Based on FTIR characterization, it was shown that these reaction conditions result in the formation of Cu(II) complexes with glycine and alanine, which are more complex structures than bis(glycinato) - and bis(alaninato) copper(II) complexes. Analysis of the FTIR spectrum of the histidine complex shows the participation of several groups in coordination at the Cu(II) center. The complex prepared with melatonin shows unusual changes in the spectral region of the amidic nitrogen bonds. The latter observation is very significant for very few known metal complexes of melatonin, while the synthesis of most of them is an experimentally demanding process with simultaneous control of several parameters. The antioxidant capacity of the synthesized complexes was examined, with the CEAC range from 121.6 to 734.4 µM. The lowest values of antioxidant capacity were recorded for the copper complex with tryptophan, while the highest values were recorded for the copper complex with alanine. A high antioxidant capacity of the copper complex with melatonin (673.8 µM) was also observed.